(untitled) - Hole, John W.; John W. Hole ([Dubuque, IA], 1992)
This text provides accurate information about the structure and function of the human body, complete with case studies and scientific research essays. It is intended for use by students pursuing careers in the allied health field and who have little biological science experience. This edition includes new clinical case studies that provide students with in-depth studies to test their understanding of key concepts. There are five summary charts that compile textual material into a concise, easier to learn form. End of chapter research essays provide current information on ongoing research and there is new material on lipids, membranes, carbohydrates, hydrogen bonds, vocal sounds, cardiac cycles and nerve impulses. The human organism reference plates have been redrawn and colour coded for improved clarity
Keywords: Human physiology; Human anatomy